Putting passives in their place [PCB integration]. - Ulrich, R. (IEEE spectrum)
The next big thing in miniaturization is integrating resistors, capacitors, and inductors into circuit boards. These integrated passives would be a part of the circuit board itself, formed when the board was, so their overall cost would eventually be less than what manufacturers pay at present to buy and solder attach discrete devices. This article examines the advantages of this integration scheme, and looks at the difficulties involved.